The impact of maternal hyper-oxygenation on foeto-placental blood flow. (3rd July 2017) - Prior, Tomas; Kumar, Sailesh
Abstract: Objective : Maternal hyperoxygenation has been reported to increase foetal oxygen saturation, and is frequently employed during intra-partum episodes of foetal compromise as a component of in utero resuscitation. However, there has been little investigation of its influence on foetal haemodynamics, particularly in appropriately grown foetuses. Methods : This cohort study was undertaken between July 2013 and November 2013. All participants underwent an ultrasound scan prior to active labour (<4 cm dilated), during which foetal biometry, umbilical and middle cerebral artery Dopplers were recorded. Doppler measurements were then repeated after a 20-min period (to act as a control for subsequent measurements after oxygen therapy). Women were then asked to breathe 60% oxygen through Venturi valve masks for 20 min, after which the Doppler measurements were repeated. Results : Twenty women were recruited to the study. No significant change in the foetal cerebro-umbilical (CU) ratio was observed following maternal oxygen therapy. The degree of change in Doppler parameters after oxygen therapy was not related to the baseline value of the Doppler parameter. Conclusion : Maternal hyperoxygenation using 60% oxygen concentration over a 20-min period does not influence foetal umbilical or middle cerebral artery Doppler in appropriately grown foetuses. No adverse effects of maternal oxygen therapy were observed.